2011
DOI: 10.4067/s0718-221x2011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the operating variables of acetosolv pulping on pulp properties of oil palm frond fibres

Abstract: The effect of acetosolv pulping variables viz. pulping time, temperature, catalyst (HCl) and acetic acid on oil palm frond fibres was investigated. The following conditions were found to be optimum to pulp frond fibres: 140 ºC, 0.5% HCl, 75% acetic acid, and 1/10 solid/liquor ratio. Under these conditions we could obtain these properties: Kappa number 13-16, zero-span tensile breaking length -83 km, sheet density -0.57 g cm -3 , tensile index -48 N m g -1 , tear index -5.4 mN m 2 g-1, brightness -16% ISO and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…The ethanol extracts by the soxhlet method were 3%, containing oil, waxes, fats, and resin, and they were comparable to a previous study (Fahma et al 2010). The α-cellulose content of the isolated OPEFB cellulose was 93.7%, which is comparable to the reported value of 97.1% (Leh et al 2008), but higher than 62.3% (Wanrosli et al 2011). Further delignification with performic acid effectively removed the lignin and the hemicelluloses fraction, and produced a total cellulose yield of 64% (w/w) on a dry weight basis, which was higher than the previously reported yield at 44.4% (Sun et al 1999) and 60.6% (Wanrosli et al 2004) using chlorite and sodium hydroxide, respectively.…”
Section: Extraction Of Opefb-cellulosesupporting
confidence: 84%
“…The ethanol extracts by the soxhlet method were 3%, containing oil, waxes, fats, and resin, and they were comparable to a previous study (Fahma et al 2010). The α-cellulose content of the isolated OPEFB cellulose was 93.7%, which is comparable to the reported value of 97.1% (Leh et al 2008), but higher than 62.3% (Wanrosli et al 2011). Further delignification with performic acid effectively removed the lignin and the hemicelluloses fraction, and produced a total cellulose yield of 64% (w/w) on a dry weight basis, which was higher than the previously reported yield at 44.4% (Sun et al 1999) and 60.6% (Wanrosli et al 2004) using chlorite and sodium hydroxide, respectively.…”
Section: Extraction Of Opefb-cellulosesupporting
confidence: 84%
“…This could be due to the caramelization of hemicellulose in water‐less solution (solvent ratio = 0.8) which end up as an insoluble residue in lignin analysis. Furthermore, it is reported that lignin tends to re‐condensate at elevated temperature . As a result, both hemicelluloses caramelization and lignin re‐condensation are complementary and in turn rendering in low lignin removal at eminent temperature and solvent ratio.…”
Section: Resultsmentioning
confidence: 99%
“…This pulping technique is regarded as environmentally friendly which fractionate raw materials and recover the lignin and water soluble components including organosolv solvent, leading to less water pollution [49]. Wanrosli et al [74] investigated the effect of pulping temperature, HCl catalyst, and acetic acid on OPF-pulp properties. Aforementioned investigations encouraged the Acetosolv pulping technique on OPF.…”
Section: Pulp and Paper Industrymentioning
confidence: 99%
“…Aforementioned investigations encouraged the Acetosolv pulping technique on OPF. Wanrosli et al [74] investigated the effect of pulping temperature, HCl catalyst, and acetic acid on OPF-pulp properties. The findings revealed that zero-span tensile breaking length (83 km), sheet density (0.57 g/cm 3 ), tensile index (48 Nm/g), tear index (mN m 2 /g), brightness (16%), and opacity (98%) at optimum conditions of 1408C, 0.5% HCl, 75% acetic acid, and 1/10 solid/liquor ratio.…”
Section: Pulp and Paper Industrymentioning
confidence: 99%